Profiling the peripheral blood T cell receptor repertoires of gastric cancer patients - Wang, Mengyao; Gao, Peng; Ren, Laifeng; Duan, Jingjing; Yang, Silu; Wang, Haina; Wang, Hongxia; Sun, Junning; Gao, Xiaoyan; Li, Bo; Li, Shuaicheng; Su, Wen (Frontiers in Immunology, 2022)
Cancer driven by somatic mutations may express neoantigens that can trigger T-cell immune responses. Since T-cell receptor (TCR) repertoires play critical roles in anti-tumor immune responses for oncology, next-generation sequencing (NGS) was used to profile the hypervariable complementarity-determining region 3 (CDR3) of the TCR-beta chain in peripheral blood samples from 68 gastric cancer patients and 49 healthy controls. We found that most hyper-expanded CDR3 are individual-specific, and the gene usage of TRBV3-1 is more frequent in the tumor group regardless of tumor stage than in the healthy control group. We identified 374 hyper-expanded tumor-specific CDR3, which may play a vital role in anti-tumor immune responses. The patients with stage IV gastric cancer have higher EBV-specific CDR3 abundance than the control. In conclusion, analysis of the peripheral blood TCR repertoires may provide the biomarker for gastric cancer prognosis and guide future immunotherapy.